2015
DOI: 10.4085/1062-6050-51.1.09
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Rates of Reliable Change Indices for Concussion Test Batteries: A Monte Carlo Simulation

Abstract: Background: Neurocognitive testing is widely performed for the assessment of concussion. Athletic trainers can use preseason baselines with reliable change indices (RCIs) to ascertain whether concussed athletes' cognitive abilities are below preinjury levels. Although the percentage of healthy individuals who show decline on any individual test is determined by its RCI's confidence level (eg, 10% false-positive rate using an RCI with an 80% confidence interval), the expected rate of 1 or more significant RCIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…First, the clinical manifestations of SRC are most prominent immediately after injury and demonstrate rapid recovery even within the first hours post-injury at a group level (McCrea et al, 2003). Indeed, our findings are consistent with prior meta-analyses of the magnitude of neurocognitive changes after SRC (Belanger & Vanderploeg, 2005; Broglio & Puetz, 2008) and with what is known about the rapid clinical recovery course after concussion (for a review, see Nelson, Janecek, & McCrea, 2013). An alternative viewpoint is that impairments persist further out from injury but that these CNTs simply lack the sensitivity to detect the abnormal signal.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…First, the clinical manifestations of SRC are most prominent immediately after injury and demonstrate rapid recovery even within the first hours post-injury at a group level (McCrea et al, 2003). Indeed, our findings are consistent with prior meta-analyses of the magnitude of neurocognitive changes after SRC (Belanger & Vanderploeg, 2005; Broglio & Puetz, 2008) and with what is known about the rapid clinical recovery course after concussion (for a review, see Nelson, Janecek, & McCrea, 2013). An alternative viewpoint is that impairments persist further out from injury but that these CNTs simply lack the sensitivity to detect the abnormal signal.…”
Section: Discussionsupporting
confidence: 90%
“… 3 As has been thoroughly examined in another report on the larger baseline sample from this study (Nelson et al, 2015), MSVT failure was rare and demonstrated poor agreement with the validity output of any CNT. Thus, given our goal to examine the performance of these CNTs in their typical clinical context (in which only the CNT validity criteria are available, and because the MSVT does not appear to measure the same construct as related to performance validity as the CNTs measure, and, we did not exclude subjects from the primary analyses due to failure to pass the MSVT at baseline ( n =3 in this sample).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…It is important to note that our concise cognitive battery is less susceptible to false-positive classification as "cognitive decline" with the RCI method because the false-positive rate increases with longer test batteries. 22 Definition of 1-Year Poor Cognitive Outcome Our primary definition of poor 1-year cognitive outcome was cognitive impairment (≥1 score on ≥2 of 3 tests meeting criteria for impairment), cognitive decline (≥1 score on ≥2 of 3 tests meeting criteria for decline), or both. This cognitive outcome categorization for each patient with mTBI and control participant was visualized by first stratifying the cohort by 1-year cognitive impairment status and then plotting the RCI used to determine cognitive decline categorization for each patient (i.e., RCI from the test with the second greatest decline).…”
Section: Definition Of Cognitive Declinementioning
confidence: 99%